THE IDEA OF LATIN AMERICAN UNITY FROM THE PERSPECTIVE OF PERIPHERAL MIDDLE SCHOOL POETS - Fregoso Bailon, Raul Olmo; Lara, Gilberto, P.; Leija, María (Revista Tempos e Espaços em Educação, 2019)
This research shows how a group of students from a middle school in one of the poorest and violent neighborhoods in Guadalajara, México, make poems to express how they experience and signify the idea of Latin American unity in light of non-Western, perspectives. Drawing from Latin American philosophers such as Simón Rodríguez and Ramón Xirau, the method of this study draws from poetic images to construct theoretical arguments in education to analyze the poems produced by the students as active creators of Latin American epistemology in education. The findings suggest that the students as peripheral poets can enrich the foundations of critical pedagogy for Latin American unity. Of particular interest is the way in which the students challenge the distinction between colonialism and coloniality of power. This paper aims to show how Western critical pedagogy can be enriched by taking into account thinkers on education from the “Third World.”